Chemical composition and hypocholestrolemic effects of white rice, brown rice and germinated brown rice (Oryza sativa l.) in atherosclerosis-induced rabbits - Abdul Kadir, Khairul Kamilah (2012)
Many studies have reported the beneficial effect of BR consumption which mostly related to the bran layer of the rice kernels. Germinated brown rice (GBR), an improved product of BR is simply produced by soaking BR in water for certain duration. Even though the beneficial effect of germinated seeds has been well established, however the cardioprotective effect of GBR is still unknown. Therefore, this study was conducted to analyze nutritional value and antioxidant activity of WR, BR and GBR and to determine the cardioprotective effect of WR, BR and GBR-containing diets against hypercholesterolemia in hypercholesterolemic-induced rabbits. Proximate analyses of WR, BR and GBR were determined by AOAC (1996) methods. Minerals content were analyzed using atomic absorption spectrophotometer (AAS). Antioxidant activity was determined by free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric thiocyanate (FTC) and thiobarbituric acid (TBA) methods. Forty two male New Zealand white (NZW) rabbits were used and grouped as; NC (normal diet, n=7), PC (normal diet enriched with 0.5% cholesterol, n=7), WR (30% of white rice enriched with 0.5% cholesterol, n = 7), BR (30% of brown rice enriched with 0.5% cholesterol, n=7), GBR (30% of germinated brown rice enriched with 0.5% cholesterol, n=7) and SG (simvastatin enriched with 0.5% cholesterol, n=7). Blood samples were collected for plasma lipid analyses, antioxidant enzymes, plasma liver toxicity enzymes and total antioxidant status at week 0, 5 and 10 respectively while the aorta was excised for assessment of atherosclerotic plaques and histological observation at termination. The BR and GBR sample presents a significantly higher content of ash (1.44%) than WR (0.56%) (p<0.05) as a result of high amount of minerals such as natrium and calcium. Germinated brown rice also contain high levels of protein (8.4%), dietary fiber (11.2%) and fat (2.57%); which were significantly higher compared to WR but significantly lower than that of BR (p<0.05). The high level of fat in GBR was balanced with the composition of monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA). The BR and GBR also showed high content of tocopherol, tocotrienol and oryzanol compared to WR (p<0.05). Brown rice and GBR expressed the highest antioxidative activities in comparison to that of WR in FTC and TBA methods, meanwhile DPPH assay denoted strong antioxidant activity in GBR with lower IC50 at 204μg/ml compared to that of WR and BR. Plasma samples of BR and GBR-fed rabbits showed low levels of total cholesterol (TC) and low density liporprotein (LDL) than other groups at week 10 (p<0.05). High density lipoprotein (HDL) also was highest in GBR-fed rabbits compared to other treated groups (p<0.05). Feeding rabbits with GBR also reveals a favourable effect towards a reduction of atherosclerosis in the aorta by 70%. The aorta of rabbits fed with GBR also showed the nonexistence of foam cell when observed with Transmission Electron Microscope (TEM), comparable with the NC and SG groups. As a conclusion, the nutritive value of BR and GBR appeared to be responsible for the reduction of cholesterol levels and procrastinating the atherosclerotic plaque formation in rabbits induced with high cholesterol-diet. GBR was found to be more effective anti-atherogenic agents compared to WR and BR. Therefore, BR and GBR possess a strong preventive effect against free radical-mediated diseases such as cardiovascular disease (CVD), atherosclerotic disease or coronary heart disease.